Preparation method of diphenylketone-containing glycidyl ether and DCP (dicumyl peroxide) bi-crosslinked EAA (ethylene acrylic acid) and LDPE (low-density polyethylene) cable material

By using the dual crosslinking system of LDPE and EAA in insulated cable materials, DCP and 4,4'-dihydroxybenzophenone diglycidyl ether as crosslinking agents, the additives in existing cable materials are solved. The defects and problems significantly improve the mechanical and electrical properties of the cable.

CN119431834AActive Publication Date: 2025-02-14HARBIN UNIV OF SCI & TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411557512.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-02
Publication Date
2025-02-14
Estimated Expiration
2044-11-02

Smart Images

  • Figure HDA0005116928600000011
    Figure HDA0005116928600000011
  • Figure HDA0005116928600000012
    Figure HDA0005116928600000012
  • Figure HDA0005116928600000021
    Figure HDA0005116928600000021
Patent Text Reader

Abstract

The invention relates to a preparation method of a diphenylketone-containing glycidyl ether and DCP bi-crosslinked EAA and LDPE cable material, and belongs to the technical field of high-voltage direct-current cables. The preparation method of the diphenylketone-containing glycidyl ether and DCP bi-crosslinked EAA and LDPE cable material comprises the following steps: by taking an ethylene acrylic acid copolymer (EAA) and low-density polyethylene (LDPE) as matrixes, and taking a small-molecule epoxy compound 4, 4 '-dihydroxybenzophenone diglycidyl ether and DCP as crosslinking agents, carrying out crosslinking reaction on the EAA and the LDPE, so as to prepare the diphenylketone-containing glycidyl ether and DCP bi-crosslinked EAA and LDPE cable material. And heating and pressurizing on a plate vulcanizing machine to obtain the double-crosslinking type high-voltage direct-current cable material. The preparation method of the double-crosslinking type high-voltage direct-current cable material is simple, and the breakdown performance and the tensile property of the high-voltage cable material are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a double-crosslinked EAA and LDPE cable material containing glycidyl ether of benzophenone and DCP, and belongs to the technical field of high-voltage direct current cable material preparation. Background Art

[0002] At present, most of the insulated cable materials at home and abroad are prepared with low-density polyethylene as the main component, and various additives such as voltage stabilizers, antioxidants, and cross-linking agents are added. Due to the poor mechanical properties of low-density polyethylene, in order to enhance the mechanical properties of polyethylene, the traditional method is to add a cross-linking agent DCP to make it undergo a cross-linking reaction to form cross-linked polyethylene (XLPE). However, the addition of DCP, voltage stabilizers, cross-linking agents and other additives will cause defects in the material, thereby causing the performance of the cable to deteriorate. In order to ensure the purity of the cable material, it is necessary to reduce the use of other additives while ensuring the excellent performance of polyethylene.

[0003] The present invention uses LDPE and EAA as base resins, and uses DCP and 4,4'-dihydroxybenzophenone diglycidyl ether as dual crosslinking agents, so that LDPE and EAA undergo free radical crosslinking and nucleophilic addition crosslinking simultaneously. When the dual crosslinking system is formed, voltage-stabilizing fragments and electron deep traps are introduced in situ, thereby avoiding the addition of other small molecule additives, and significantly improving the mechanical and electrical properties of the cable material. Summary of the invention

[0004] The invention discloses a method for preparing a double cross-linked EAA and LDPE cable material containing glycidyl ether of benzophenone and DCP, which is characterized in that a certain amount of low-density polyethylene LDPE, small molecule 4,4'-dihydroxybenzophenone diglycidyl ether, ethylene acrylic acid copolymer EAA and dicumyl peroxide DCP are added into a torque rheometer for melt blending to obtain a mixed material; the mixed material is pressed and formed in a flat vulcanizer, and then the temperature is increased for cross-linking, and after cooling, a high-voltage direct current cable material LEBD with significantly improved breakdown strength and tensile properties is obtained.

[0005] Furthermore, the amount of DCP is 1.6% of the mass of LDPE, and the mass of the 4,4'-dihydroxybenzophenone diglycidyl ether / EAA / LDPE blend material contains: 5%-11% by mass of EAA, 85%-94% by mass of LDPE, and 1.6%-3.8% by mass of 4,4'-dihydroxybenzophenone diglycidyl ether.

[0006] One of the purposes of the present invention is to provide a method for preparing the composite material, the method comprising the following steps:

[0007] S1, melt blending; blending the DCP / epoxy / EAA / LDPE composite insulation material uniformly to obtain a blended composite material;

[0008] S2, processing and molding; the blended composite material is pressed and molded in a flat vulcanizer, and then cross-linked under pressure, and then placed in a vacuum drying process after cooling to obtain a high-voltage insulating cable material LEBD.

[0009] It is further defined that S1 is specifically as follows: LDPE is added into a torque rheometer, melted at 115°C, the rotation speed is 60r / min, and after mixing for 5 minutes, EAA and the epoxy compound 4,4'-dihydroxybenzophenone diglycidyl ether are added and mixing is continued for 10 minutes, and finally DCP is added and mixed for 3 minutes to obtain a blended composite material.

[0010] It is further defined that the pressing temperature in S2 is 115° C. and the pressure is 15 MPa.

[0011] It is further defined that the pressure cross-linking temperature in S2 is 175° C. and the pressure is 15 MPa.

[0012] It is further defined that the vacuum drying treatment temperature in S2 is 80° C. and the time is 24 h.

[0013] A second object of the present invention is to provide an application of the composite material mentioned above, specifically the composite material is used to make a high voltage DC cable.

[0014] The present invention has the following beneficial effects:

[0015] (1) The present invention designs a benzophenone-type small molecule epoxy compound that can be cross-linked with a carboxyl-containing polymer and fused with XLPE to form a double cross-linked system, which significantly improves the mechanical tensile properties of the material.

[0016] (2) The present invention introduces a benzophenone structure that can effectively "capture" electrons into the cable material in a cross-linked manner, and simultaneously introduces deep electron traps in situ, thereby significantly enhancing the DC breakdown performance of the high-voltage DC cable material.

[0017] (3) The LEBD composite insulation material prepared by the present invention has a simple preparation process, low cost, and easy-to-obtain materials, and has prospects for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 Infrared spectrum test diagram of LEBD high voltage DC cable materials provided by different embodiments;

[0019] Figure 2 Thermal elongation diagram of LEBD high voltage DC cable materials provided in different embodiments;

[0020] Figure 3 Tensile test result curves of LEBD high voltage DC cable materials provided in different embodiments;

[0021] Figure 4 Weibull distribution diagram of DC breakdown field strength of LEBD high voltage DC cable materials provided in different embodiments; DETAILED DESCRIPTION

[0022] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.

[0023] The process of preparing the DCP / epoxy / LDPE / EAA modified composite material in this example is as follows:

[0024] Embodiment 1:

[0025] (1) Melt blending: 37.33 g of LDPE was added to a torque rheometer and melted at 115 °C at a speed of 60 r / min. After mixing for 5 min, 2 g of EAA and 0.67 g of epoxy compound 4,4'-dihydroxybenzophenone diglycidyl ether were added and mixing continued for 10 min. Finally, 0.59 g of DCP was added and mixed for 3 min to obtain a blended composite material in which the EAA content was 5%.

[0026] (2) Processing: The blended composite material was pressed in a flat vulcanizer at a temperature of 115°C and a pressure of 15 MPa, and then pressed for 30 min at a temperature of 175°C and a pressure of 15 MPa to complete crosslinking, thereby obtaining LE5BD. 1.6 High voltage DC cable materials.

[0027] Embodiment 2:

[0028] (1) Melt blending: 36.25 g of LDPE was added into a torque rheometer, melted at 115 °C, with a rotation speed of 60 r / min, and mixed for 5 min. Then, 2.8 g of EAA and 0.95 g of epoxy compound 4,4'-dihydroxybenzophenone diglycidyl ether were added and mixed for 10 min. Finally, 0.58 g of DCP was added and mixed for 3 min to obtain a blended composite material in which the EAA content was 7%.

[0029] (2) Processing: The blended composite material was pressed in a flat vulcanizer at a temperature of 115°C and a pressure of 15 MPa, and then pressed for 30 min at a temperature of 175°C and a pressure of 15 MPa to complete crosslinking, thereby obtaining LE7BD. 1.6 High voltage DC cable materials.

[0030] Example 3

[0031] (1) Melt blending: 35.18 g of LDPE was added to a torque rheometer and melted at 115 °C at a speed of 60 r / min. After mixing for 5 min, 3.6 g of EAA and 1.22 g of epoxy compound 4,4'-dihydroxybenzophenone diglycidyl ether were added and mixing continued for 10 min. Finally, 0.56 g of DCP was added and mixed for 3 min to obtain a blended composite material in which the EAA content was 9%.

[0032] (2) Processing: The blended composite material was pressed in a flat vulcanizer at a temperature of 115°C and a pressure of 15 MPa, and then pressed for 30 min at a temperature of 175°C and a pressure of 15 MPa to complete crosslinking, thereby obtaining LE9BD. 1.6 High voltage DC cable materials.

[0033] Embodiment 4:

[0034] (1) Melt blending: 34.11 g of LDPE was added into a torque rheometer and melted at 115 °C at a speed of 60 r / min. After mixing for 5 min, 4.4 g of EAA and 1.49 g of epoxy compound 4,4'-dihydroxybenzophenone diglycidyl ether were added and mixing continued for 10 min. Finally, 0.54 g of DCP was added and mixed for 3 min to obtain a blended composite material in which the EAA content was 11%.

[0035] (2) Processing: The blended composite material was pressed in a flat vulcanizer at a temperature of 115°C and a pressure of 15 MPa, and then pressed for 30 min at a temperature of 175°C and a pressure of 15 MPa to complete crosslinking and obtain LE 11 BD 1.6 High voltage DC cable materials.

[0036] Embodiment 5:

[0037] (1) Melt blending: 36.4 g of LDPE was added into a torque rheometer, melted at 115°C, with a rotation speed of 60 r / min, and mixed for 5 min, and then 3.6 g of EAA was added and mixed for 10 min to obtain a blended composite material, wherein the EAA content was 9%.

[0038] (2) Processing and molding: The blended composite material is pressed in a flat vulcanizer at a temperature of 115°C and a pressure of 15 MPa, and then pressed at a temperature of 110°C and a pressure of 15 MPa for 30 minutes to complete cross-linking, thereby obtaining the LE9 high-voltage DC cable material.

[0039] Embodiment 6:

[0040] (1) Melt blending: 35.18 g of LDPE was added to a torque rheometer, melted at 115°C, with a rotation speed of 60 r / min, and mixed for 5 min. 3.6 g of EAA and 1.22 g of epoxy compound 4,4'-dihydroxybenzophenone diglycidyl ether were further mixed for 10 min to obtain a blended composite material, wherein the EAA content was 9%.

[0041] (2) Processing and molding: The blended composite material is pressed in a flat vulcanizer at a temperature of 115°C and a pressure of 15 MPa, and then pressed at a temperature of 110°C and a pressure of 15 MPa for 30 minutes to complete cross-linking, thereby obtaining the LE9B high-voltage DC cable material.

[0042] Embodiment 7:

[0043] (1) Melt blending: 36.4 g LDPE was added into a torque rheometer and melted at 115 °C at a rotation speed of 60 r / min. After mixing for 5 min, 3.6 g EAA was added and mixing was continued for 10 min. Finally, 0.58 g DCP was added and mixed for 3 min to obtain a blended composite material in which the EAA content was 9%.

[0044] (2) Processing and molding: The blended composite material was pressed in a flat vulcanizer at a temperature of 115°C and a pressure of 15 MPa, and then pressed for 30 min at a temperature of 175°C and a pressure of 15 MPa to complete crosslinking, thereby obtaining LE9D 1.6 High voltage DC cable materials.

[0045] The performance tests were performed on the benzophenone-type small molecule epoxy compounds and DCP double cross-linked XLPE high-voltage DC cable materials with different contents prepared in the above Examples 1 to 4, and the specific test results are as follows:

[0046] (1) The molecular structure of the above materials was tested, analyzed and characterized by Fourier transform infrared spectrometer (FT / IR 6100) to verify whether they successfully participated in the cross-linking reaction. The sample thickness selected in the experiment was 100 μm thin slices, and the test spectrum wave number range was 500-4000 cm -1 , scanning accuracy is 2cm -1 , the scanning times are 30 times, and the results are as follows Figure 1 shown.

[0047] Depend on Figure 1 It can be seen that compared with the EAA / LDPE blend material, the modified high-voltage DC cable material has a -1 A new absorption peak appeared near 1700 cm -1 The peak red-shifted to 1725 cm -1, and turned into a broad peak, corresponding to the characteristic peak of the ester group in the composite material, indicating that the cross-linking was successful.

[0048] (2) Prepare dumbbell specimens and measure cross-sectional areas according to the test method specified in GB / T 2951.11-2008. Cut the prepared modified high-voltage DC cable material sample into a dumbbell-shaped specimen with a thickness of 1 mm using a cutter. The total length is 75 mm, the width of the effective test part is 4 ± 0.2 mm, and the surface is smooth without visible defects. Use a marker to mark the narrow section with a spacing of 20 mm. The test is carried out in a 200℃ natural ventilation oven. The specimen is suspended from the upper chuck and clamped by the lower chuck. A weight is added to the lower chuck. The weight = 20.4 × specimen thickness × specimen width (including clamps, support rods and weights). The specimen is kept at 200℃ in the oven. After 15 minutes, the distance between the marking lines is measured and the elongation is calculated.

[0049] According to GB / T12527-2008, the thermal elongation of XLPE insulated cables shall not exceed 175%. Figure 2 It can be seen that the cable materials prepared in the present invention meet the standard requirements, and the thermal elongation decreases significantly with the increase of EAA. When the EAA content is 11%, the thermal elongation is only 33.8%.

[0050] (3) The above four materials were tested by SUNS UTM2203 electronic universal testing machine according to the national standard GB / T528-2009. According to the test method required by the standard, the prepared modified DCP / epoxy / EAA / LDPE composite material sample was cut into a dumbbell-shaped sample with a thickness of 1 mm using a cutter, with a total length of 75 mm and an effective test portion width of 4±0.2 mm. The surface was smooth without visible defects, and a marker pen was used to mark the narrow section with a spacing of 20 mm. The clamp spacing was set to 20 mm, the tensile rate was 250 mm / min, and each material was tested 5 times.

[0051] According to the requirements of standard GB / T22078.1-2008, the tensile strength and elongation at break of XLPE materials for high-voltage power cables should be no less than 12.5MPa and 200% respectively. Figure 3 It can be seen that under the same experimental conditions, the tensile properties of the modified high-voltage DC cable material are significantly improved, with its elongation at break reaching 1382.24% and its tensile strength reaching 31.06MPa. The elongation at break is 6.91 times higher than the standard, and the tensile strength is 2.48 times higher than the standard.

[0052] (4) The DC breakdown field strength test of the above materials was carried out at 30°C using a cylindrical electrode, with a voltage step-up rate of 1 kV / s and a sample thickness of 50 μm. The sample and the electrode were in transformer oil throughout the entire process, and 10 groups of samples were selected for repeated experiments under each experimental condition.

[0053] The two-parameter Weibull distribution is used to perform statistics on the DC breakdown strength experimental data, which is described as follows:

[0054] P(E)=1-exp(-(E / E b ) β )

[0055] Where: P(E) is the cumulative failure probability, E is the measured breakdown field strength, E b is the characteristic breakdown field strength when the breakdown probability is 63.2%, and β is the shape parameter.

[0056] The Weibull distribution of the DC breakdown strength of the above four materials is as follows: Figure 4 shown.

[0057] Depend on Figure 4 It can be seen that the DC breakdown strength of the four modified high-voltage DC cable materials has been improved to varying degrees compared to before modification. After adding epoxy compounds for modification, the breakdown field strength of each content is significantly improved. Compared with before modification, the breakdown strength of the modified high-voltage DC cable material reaches a maximum value of 430kV / mm at 9% EAA content, which is higher than that of pure LDPE, LE9, and LE9D. 1.6 The four blank components of LE9B increased by 42.33%, 23.57%, 5.31% and 13.32% respectively. The high-voltage DC cable material with this content has good breakdown characteristics.

[0058] The above description is only a preferred embodiment of the present invention. In view of the fact that technicians in the field of the present invention can make appropriate changes and modifications to the above implementation, the present invention is not limited to the specific implementation described above. Some modifications and changes to the present invention should also fall within the scope of protection of the claims of the present invention.

Claims

1. A method for preparing a double cross-linked EAA and LDPE cable material containing glycidyl ether of benzophenone and DCP, characterized in that A certain amount of low-density polyethylene (LDPE), 4,4'-dihydroxybenzophenone diglycidyl ether, ethylene acrylic acid copolymer (EAA) and dicumyl peroxide (DCP) are added into a torque rheometer for melt blending to obtain a mixed material; the mixed material is pressed and formed in a flat vulcanizer, then heated and cross-linked, and after cooling, a high-voltage DC cable material with significantly improved breakdown strength and tensile strength is obtained.

2. The method for preparing a double cross-linked EAA and LDPE cable material containing glycidyl ether of benzophenone and DCP according to claim 1, characterized in that The components used as the crosslinking agent are 4,4'-dihydroxybenzophenone diglycidyl ether and dicumyl peroxide DCP.

3. The method for preparing a double cross-linked EAA and LDPE cable material containing glycidyl ether of benzophenone and DCP according to claim 1, characterized in that EAA accounts for 5% to 11% of the total weight of 4,4'-dihydroxybenzophenone diglycidyl ether / EAA / LDPE.

4. The method for preparing a double cross-linked EAA and LDPE cable material containing glycidyl ether of benzophenone and DCP according to claim 1, characterized in that LDPE accounts for 85%-94% of the total weight of 4,4'-dihydroxybenzophenone diglycidyl ether / EAA / LDPE.

5. The method for preparing a double cross-linked EAA and LDPE cable material containing glycidyl ether of benzophenone and DCP according to claim 1, characterized in that The content of DCP is 1.6% of the mass fraction of LDPE.

6. The method for preparing a double cross-linked EAA and LDPE cable material containing glycidyl ether of benzophenone and DCP according to claim 1, characterized in that The 4,4'-dihydroxybenzophenone diglycidyl ether accounts for 1.6%-3.8% of the total mass of 4,4'-dihydroxybenzophenone diglycidyl ether / EAA / LDPE.

7. The method for preparing a double cross-linked EAA and LDPE cable material containing glycidyl ether of benzophenone and DCP according to claim 1, characterized in that Mainly used in high voltage DC cable materials.

8. The use according to claim 7, characterized in that The prepared high-voltage DC cable material has a DC breakdown strength of up to 430.4 KV / mm and a tensile elongation at break of up to 1008.4%-1382.24%.

Citation Information

Patent Citations

  • Polyethylene material capable of crosslinking in natural light as well as preparation method and using method thereof

    CN103113655A

  • Grafting modified crosslinked polyethylene insulating layer and preparation method and application thereof

    CN115028775A

  • Crosslinked polyethylene insulating material as well as preparation method and application thereof

    CN116178824A

  • Preparation and application of epoxy cross-linked LLDPE / EAA composite insulating material

    CN117362693A

  • Polymer composite material based on chain scission-dynamic crosslinking strategy as well as preparation method and application of polymer composite material

    CN118165478A